The 2021-22 Merchant Acceptance Survey pilot study - Angelika Welte; Joy Wu (Bank of Canada, 2023)
In recent years, the rise in digital payment innovations such as contactless cards and Interac e-Transfer has spurred a discussion about the future of cash at the point of sale. The COVID19 pandemic has also contributed to this discussion: While consumers reported that some merchants started to refuse cash early in the pandemic, such reported refusals dropped as the pandemic progressed. The Bank of Canada's most recent Merchant Acceptance Survey (MAS) took place in 2018, prompting a need for updated data to study merchant cash acceptance, payment trends and conditions for the potential issuance of a central bank digital currency (Lane 2020, 2021a). Against this background, the Bank conducted the 2021-22 MAS Pilot Study to monitor payment methods accepted by small and medium-sized businesses (SMBs). Survey data was collected from merchants in two batches, in late 2021 and early 2022. Our results show that 97% of SMBs in Canada accepted cash in 2021-22 and only 3% have plans to stop accepting cash. For cards and digital payments, merchant acceptance has increased since 2018. Additionally, the acceptance of different payment methods varies by the size of the merchant, industry and region.
Keywords: C8; D22; E4; L2; 330; Bank notes; Digital currencies and fintech; Econometric and statistical methods